PERMASALAHAN PADA PELAKSANAAN PEMBELAJARAN TERINTEGRASI DI PROGRAM STUDI PENDIDIKAN BAHASA JEPANG, UNDIKSHA - Hermawan, Gede Satya; Krishna Adnyani, Kadek Eva (Universitas Pendidikan Ganesha, 2018)
The issue of integrated learning on the basic Japanese language skills, namely: Bunpou,Choukai, and Kaiwa, had been raised since the establishment of the Japanese Education Department. Arecent evaluation study found that in the actual implementation of this integrated learning experience,a number of problems need to be considered for the quality of learning process in the Department ofJapanese Language Education. The problems discussed in this paper are related to the implementationof integrated courses and the issues that follow. This research conducted in the Bunpou, Choukai,and Kaiwa classes in the 2016/2017. This study used a descriptive qualitative method with observationand interviews techniques. The results found that problems in implementing this integrated learningcomprise: lecturers’ communication skills, conflicted time with other activities, and different teachingthemes from one lecturer to the other lecturers.Keywords : Bunpou, Choukai, Kaiwa, integrated learning, Department of Japanese Language Education.